Emission lifetime study of fluorescence probes based on G-quadruplex oligonucleotides end-labeled with pyrene moieties. Issue 3 (2010) - Cupane Cupane, A. A.; Dembska Dembska, A. A.; Pedzinski Pedzinski, T. T.; Takenaka Takenaka, S. S.; Juskowiak Juskowiak, B. B.
Abstract : Fluorescence lifetime study of two probes abbreviated as Py-Htelom-Py and Py-TBA-Py, carrying pyrene moieties at both termini and sequences of Human telomere and Thrombin Binding Aptamer, respectively are reported. The effect of potassium ion on the photophysical processes was examined in order to elucidate factors that facilitate the production of excimer emission. Emission kinetics data indicated that the relative orientation of pyrene and neighboring nucleobase (guanine, adenine, thymine) plays a crucial role in determining both the rate of electron-transfer quenching of pyrene excited state and the efficiency of excimer emission.